Musical preferences during and after relaxation and exercise - North, Adrian; Hargreaves, David (University of Illinois Press, 2000)
Effects of the listening context on responses to music largely have been neglected despite the prevalence of music listening in our everyday lives. This article reports 2 studies in which participants (college students) chose music of high or low arousal potential during (Exp 1) or immediately after (Exp 2) exercise or relaxation. In Exp 1, participants preferred appropriate arousal-polarizing music over arousal-moderating music. In Exp 2, participants preferred arousal-moderating music over arousal-polarizing music, such that their listening times contrasted clearly with those in the first study even though the same music and methods were used. Thus, musical preferences interact with the listening situation, and participants' music selections represent an attempt to optimize their responses to that situation. When motivated to maintain a state of polarized arousal, listeners use music to achieve this; when they have no such goal, they use music to moderate arousal.